THE FACTORS THAT INFLUENCE MIDWIVES TO EXAMINING THEMSELVES THROUGH PAP SMEAR EXAMINATION AT GENERAL Dr. PIRNGADI HOSPITAL MEDAN CITY IN 2020 - friska apriani sihombing (Jurnal Inovasi Kesehatan Masyarakat, 2020)
Cervical cancer is killer cancer that most often attacks women who cause death. One of the efforts for early detection of cervical cancer is by conducting a pap smear examination. According to WHO cervical cancer is the second most common type of cancer in Indonesia as many as 32,469 cases or 9.3%. The purpose of this study was to determine the factors that influence midwives to examining themselves through pap smear examination at general Dr. Pirngadi hospital Medan City in 2020. The study method used observational analytic with cross-sectional approach. This research was conducted at genera Dr. Pirngadi hopital Medan city from January to March 2020. The population in this study were all health workers who work as midwives and the sample was 83 people. Data analysis with Chi Square and Multiple Logistic Regression. The results showed 53.0% have a pap smear examination and 47.0% have no a pap smear examination. There is a significant relationship between husband's support and length of work on pap smear p